2021
DOI: 10.3390/foods10051147
|View full text |Cite
|
Sign up to set email alerts
|

Metal Contents in Fish from the Bay of Bengal and Potential Consumer Exposure—The EAF-Nansen Programme

Abstract: Fish represent an important part of the Sri Lankan and Bangladeshi diet. However, fish is also a source of contaminants that may constitute a health risk to consumers. The aim of this study was to analyse the contents of arsenic, cadmium, mercury, and lead in 24 commonly consumed marine fish species from the Bay of Bengal and to assess the potential health risk associated with their consumption. Mercury and lead contents did not exceed the maximum limits for any of the sampled species, and consumer exposure fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A recent study conducted by Reksten et al . (2021) [ 68 ] found that small marine fish from Bangladesh and Sri Lanka had higher levels of cadmium, arsenic, and lead than large fish, though large fish had higher mercury levels. However, they concluded that studied marine fish posed no health risks to adults and children when consumed in the recommended amounts.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted by Reksten et al . (2021) [ 68 ] found that small marine fish from Bangladesh and Sri Lanka had higher levels of cadmium, arsenic, and lead than large fish, though large fish had higher mercury levels. However, they concluded that studied marine fish posed no health risks to adults and children when consumed in the recommended amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Fatema et al 63 found that the mercury concentration in the Gher and river shrimp samples was below the acceptable level. Using samples taken from Bangladeshi maritime waters, Moxness Reksten et al 69 examined the levels of arsenic, cadmium, mercury and lead in 24 distinct marine fish species from the Bay of Bengal. They discovered that mercury levels in fish of all species were significantly lower than the EU regulatory limits.…”
Section: Findings From Prior Literaturementioning
confidence: 99%
“…Fatema et al 63 found that the mercury concentration in the Gher and river shrimp samples was below the acceptable level. Using samples taken from Bangladeshi maritime waters, Moxness Reksten et al 69 The Ordinance provides the Government the power to set grades, quality and standards of fish and fish products for ensuring nutrition security. Penalties for violations have also been specified.…”
Section: Mercury Concentrationmentioning
confidence: 99%
“…Food safety is an issue of global concern, which makes it essential to determine the toxic elements in foods and their toxicological effects on human health. Therefore, organisations such as the World Health Organization (WHO), Food and Agriculture Organization (FAO), Environmental Protection Agency (EPA), and European Commission (EC) set maximum acceptable levels on foods in order to protect the health of consumers and promote good practices in the food trade [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%